PENGARUH PANDEMI TERHADAP TATA KELOLA PEMERINTAHAN; STUDI KASUS PELAYANAN PUBLIK PEMERINTAH PROVINSI LAMPUNG - Ridwan Saifuddin (Balitbangda Provinsi Lampung, 2021)
The COVID-19 pandemic has had an impact on the delivery of public services. Various adjustments and arrangements have been made by regional apparatus that provide public services within the Lampung Provincial Government. The capacity of regional apparatus organizations, especially those related to public services, still needs to be improved. The identification of impacts and alternative responses that are important for public service organizations in dealing with this pandemic is reviewed using qualitative research methods. The results of interviews using questionnaires with civil servant respondents who provide public services in the local government of Lampung Province show that the main obstacles in improving the quality of public services that are important to be addressed immediately are related to the capacity of human resources of the apparatus, supporting infrastructure for public services, utilization of information and communication technology that is more optimal, and commitment of leaders in realizing higher quality organizations and public services. Integrated governance and proper investment in human resources, technology, and managerial aspects are increasingly urgent to be realized. The mechanism of interaction and connectivity between providers and users of public services also still needs to be improved, so that it is hoped that the government and the community will be closer, synergies can be stronger, and new initiatives will be more facilitated. The public needs to be more involved in efforts to improve the quality of public services provided by the government.